Apoptotic effect of Physalis minima Linn ethanol extract on breast cancer cells via p53 wild-type and Apaf-1 protein - Handayani, Handayani (University of Benin, 2020)
Abstract Purpose: To produce an anti-cancer agent from Physalis minima ethanol extract as well as prevent the growth of NMU-induced breast cancer and MCF-7 cell line. Methods: This research used an animal model (Wistar-Furth rats), and cell line used in this study was normal breast-cell line MCF-7. The rats were administered with the ethanol extract of Physalis minima Linn (100, 250 and 400 mg/kg/day) by gavage, once a day for 4 weeks. Meanwhile, MCF-7 cell lines were cultured in medium and incubated in 100 μg/mL of ethanol extract of Physalis minima for 48 h. The samples were analyzed using histology and immunohistochemistry techniques for expression of p53 antibody DO-1 and APAF-1. Results: The results of immunohistological analysis in the breast organ showed that Physalis minima Linn extract significantly (p < 0.05) increased the tumor suppressor protein p53 at doses of 100, 250 and 400 mg/kg/day. In addition, the extract also significantly (p < 0.05) increased APAF-1, which is a gene determining cell death, at doses of 100, 200 and 400 mg/day. Conclusion: Ethanol extract of Physalis minima Linn inhibits the cytotoxic activity of NMU-induced breast cancer by increasing the tumor suppressor protein p53 and APAF-1. Thus, Physalis minima Linn extract can potentially be used as a complementary treatment for inhibiting the growth of breast cancer cells in patients.